Integrating Disaster Education into School Curriculum in Indonesia: A Scoping Review - Desilia, Nurul Rahmah; Lassa, Jonatan; Oktari, Rina Suryani (International Journal of Disaster Management, 2023)
Despite being one of the most disaster prone countries in the world, disaster education is not mandatory in Indonesia. Existing research suggest that predictors of schools adoption of disaster education into their curriculum have been subject to school leadership, discretion of teachers, incentives and nudges, among others. This systematic literature review aims to understand how schools integrate disaster education into the the curriculum in Indonesia. Key research questions include: i) How has disaster education is integrated into the school curriculum in Indonesia?; ii) What content informs the curriculum in the case where disaster education integration exist in by the early adopters?; iii) What model or approach is used to integrate disaster education into the school curriculum?; iv) How effective such a disaster education in increasing students' knowledge, attitudes, and behavior? and v) What are the challenges in integrating disaster education into the school curriculum? The study also identified gaps in disaster education within the Indonesian curriculum to set an agenda for future research. Relevant literature in both English and Bahasa Indonesia from online sources, specifically Google Scholar and Science Direct databases, have been included for further analysis to explore the latest conditions and complexities in integrating disaster education into the curriculum in Indonesia. Search terms included 'disaster education', 'disaster preparedness schools', 'safe schools, curriculum', 'DRR education' 'comprehensive school safety', SPAB and other relevant keywords. The findings contribute to bridging the gap between research outcomes and practical implementation, providing recommendations for future integration practices. This research is expected to strengthen disaster education in Indonesia, enhance preparedness, and contribute to the broader field of disaster risk reduction.